От первого до последнего слова: [роман] / Татьяна Устинова - Устинова Татьяна Витальевна (Первая среди лучших, 2010)
10-11кл Экземпляры: ф.9 (20170821) / Инвентарный номер: 53899 / Цена: 50.00 / Авт.знак: У 80 / ББК: 84(2Рос-=Рус)6